Ab-initio Investigation of the Hydrogenation of Y - Koitzsch, Christian; Garnier, Michael Bernard Gunnar; Aebi, Philipp (My University, 2004)
We present an ab-initio electronic structure study of a face centred (fcc) cubic Y lattice, which is subsequently filled with hydrogen in tetrahedral and octahedral sites. The stoichiometry of the calculated compounds is Y, YH2tetra, YH3 and YH1octa. Upon placement of hydrogen in tetrahedral sites we note for the YH2tetra phase a new, fully occupied hydrogen related band and a redistribution in the d-band manifold at the Fermi level. Interestingly during the fcc Y → YH2tetra transition the overall topology of the Fermi surface (FS) is not changed, but we note a change in character from t2g to eg of the responsible band. It is this change to eg character which allows subsequent H in octahedral sites to significantly interact with the FS, finally enabling the metal-insulator transition while reaching YH3. A placement of hydrogen solely in octahedral sites does not affect significantly the t2g d-band at the Fermi level.